Improvement in symptoms of peripheral arterial disease with sildenafil therapy. Issue 3 (August 2013) - Turtle, EJ; Drummond, ID; Webb, DJ
A 57-year-old man presented with symptoms of intermittent claudication and was diagnosed with peripheral arterial disease. He was advised to stop smoking and start a walking programme. He had a background history of hypercholesterolaemia and erectile dysfunction, for which he was taking simvastatin and phosphodiesterase type-5 inhibitor sildenafil, respectively. After starting his exercise programme, he noted that his walking distance was more than doubled on the mornings after taking sildenafil, and he has been using sildenafil primarily for shopping trips since that time. Although this single-patient self-experiment has the potential for placebo confounding, the patient was not led to expect this benefit, and there is evidence that reduced nitric oxide bioactivity plays an important role in the pathophysiology of peripheral arterial disease. Given the biological plausibility of this effect, we feel that a randomised, blinded and placebo-controlled clinical study is warranted to confirm the benefit of phosphodiesterase type-5 inhibitors in peripheral arterial disease.